Sabun Cuci Tangan Cair dari Limbah Daun Galam (Melaleuca Cajuputi) - Muh Azhari; Rudy Yoga Lesmana (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2022)
This activity aims to reduce the biomass of Galam leaf waste and provide opportunities to process waste leaves into a business for the people of Palangkaraya City. The method used is the demonstration method of making the product. Liquid hand washing soap from Galam Leaf Waste can be a solution to overcome environmental problems and open up opportunities to process waste leaves into a business.